2000
DOI: 10.1097/00007890-200005150-00023
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis in Adults Undergoing Liver Transplantation

Abstract: The value of US diagnosis in patients with PVT depends on the PVT grade, and false negative diagnoses occur only in incomplete forms of PVT (grades 1-2). The degree of PVT dictates the surgical strategy to be used, thrombectomy/low dissection in grade 1-2, mesoportal jump graft in grade 3, and a splanchnic tributary in grade 4. Taken altogether, PVT patients undergo more difficult surgery, have more postoperative complications, have higher in-hospital mortality rates, and have reduced 5-year survival rates. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
566
3
34

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(622 citation statements)
references
References 19 publications
19
566
3
34
Order By: Relevance
“…In the Nery et al study, PVT correlated with the severity of portal hypertension, but was not responsible for further liver impairment. In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 87%
See 1 more Smart Citation
“…In the Nery et al study, PVT correlated with the severity of portal hypertension, but was not responsible for further liver impairment. In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 87%
“…Multiphasic helical CT or MRI are recommended to confirm the finding and evaluate patency of the superior mesenteric vein (SMV), splenic veins, or the occurrence of portosystemic shunts. Classification of PVT is important for medical treatment and surgery and the Yerdel's classification which grades the length of portal vein involvement and its extension seems adequate [202]. PVT is classified as grade 1 when <50% of the lumen is occluded with no or minimal extension to SMV; grade 2 when >50% of the portal vein is occluded; grade 3, when the portal veins and proximal SMV are occluded; grade 4 when the portal vein and SMV thromboses extend to their distal portions.…”
Section: Portal Vein Thrombosis In Cirrhosismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Studies based on ultrasonography have reported a prevalence of 10%-28%, in unselected cirrhotic patients excluding those with hepatocellular carcinoma. [8][9][10][11] Maruyama et al did a retrospective analysis of 150 patients with hepatitis B or C related cirrhosis followed up for a median period of 66 months and reported a cumulative overall incidence of PVT of 12.8% at 1 year, 18.6% at 3 years, 20% at 5 years, and 38.7% at 8-10 years.…”
Section: Prevalencementioning
confidence: 99%
“…In contrast, degree stratification is consistently involved in the studies about outcome of invasive therapies for PVT [5][6][7][8][9] due to its close associations with operability and prognosis. Herein, diverse classifications of PVT were listed in Table 2, except for simple classification into complete and partial thrombus.…”
Section: Degree Of Portal Vein Thrombosismentioning
confidence: 99%